Growth, Morphological, and Physiological Responses to Drought Stress in Bothriochloa ischaemum - Liu, Ying; Li, Peng; Xu, Guo Ce; Xiao, Lie; Ren, Zong Ping; Li, Zhan Bin (Frontiers in Plant Science, 2017)
Water shortage in the arid-semiarid regions of China seriously hampers ecosystem construction. Therefore, elucidation of the mechanisms by which vegetation in that area responds to drought stress may enable us to improve utilization of limited water resources and thus contend with the problem of drought and water shortage. We studied Bothriochloa ischaemum, a native grass species, conducted potting control tests to compare several indicators of B. ischaemum grown under three different moisture conditions (80% ,60%,40% Field capacity represent sufficient water supply, mild water stress and serious water stress, respectively). Plant response parameters measured included biomass accumulation, root morphology, transient water use efficiency (WUE), stable carbon isotope ratio (δ13C), and stable carbon isotope discrimination (Δ13C) of various plant organs and their interrelationships. B. ischaemum had the greatest WUE under mild drought stress. However, serious drought stress resulted in considerable decline in overall biomass but substantial increase in root-to-shoot ratio and fine-root biomass. Coarse-root biomass dropped appreciably, indicating that serious drought stress leads to allocation non-uniformity of the carbon “sink.” δ13C and Δ13C of stem correlated considerably with root morphology, suggesting the feasibility of characterizing WUE, biomass, and root morphology of B. ischaemum via the stable carbon isotope approach. Our evaluation of 21 drought resistance indicators of B. ischaemum showed that under a given moisture treatment gradient one can isolate an optimal indicator to express growth, morphology, and physiology, to improve the accuracy of depicting plant drought resistance and simplify the drought resistance indicator system. This study elucidates the response mechanism of B. ischaemum to drought stress and provides theoretical support to screening of drought-resistant plants across the arid-semiarid regions of China.